A Binomial Model with Edgeworth Expansion on Particular Circumstances - Milanesi, Gastón S. (Catalan Association of Accounting and Management, 2018)
Contexts with high volatility and extreme events condition the value of the firm, its tax savings and continuity. These conditions must be contemplated for the employed valuation model. In that sense, the present paper’ basis is the classic binomial model incorporating: a) firm contingent states of continuity or dissolution; b) tax saving valuation like a basket of real options, and c) extreme events by Edgeworth transformation. The paper structures in the following manner: first it develops the binomial function changed with the Edgeworth extension and the construction of implicit binomial lattice. Then it develops a valuation adapted to the binomial model with Edgeworth expansion that incorporates contingent tax savings, continuity or liquidation scenarios and cost of bankruptcy. With a hypothetical case it is illustrated its functioning, and comparing the results obtained between situations with kurtosis and skewness or normally. Finally the main conclusions are exposed.